Ursolic acid and its derivative inhibit protein tyrosine phosphatase 1B, enhancing insulin receptor phosphorylation and stimulating glucose uptake - Zhang, Wei; Hong, Di; Zhou, Yueyang; Zhang, Yinan; Shen, Qiang; Li, Jing-ya; Hu, Li-hong; Li, Jia (Biochimica et biophysica acta, 2006)
Protein tyrosine phosphatase 1B (PTP1B) is a key element in the negative regulation of the insulin signaling pathway and may play an important role in diabetes and obesity. We identified ursolic acid, a natural pentacyclic triterpenoid that occurs widely in traditional Chinese medicinal herbs, as an inhibitor of PTP1B by screening an extract library of the traditional Chinese medicinal herbs used a diabetes clinic. By modifying urosolic acid, we designed and synthesized a derivative with a K i of 283 nM. As competitive inhibitors of PTP1B, ursolic acid and its derivative also inhibit T-cell protein tyrosine phosphatase and src homology phosphatase-2 but not leucocyte antigen-related phosphatase or protein tyrosine phosphatase α and ε, which are all possibly involved in the insulin pathway. The ursolic acid derivative enhanced insulin receptor phosphorylation in CHO/ hIR cells and stimulate glucose uptake in L6 myotubes.